2017
DOI: 10.4236/fns.2017.82019
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Fructooligosaccharide Mildly Improves the Iron Status of Anemic Rats Fed a Low-Iron Diet

Abstract: Also known as a prebiotic, fructooligosaccharide (FOS) resists digestion by gastric acid and pancreatic enzymes in vivo, but is preferentially fermented by beneficial intestinal bacteria once it reaches the colon. While some studies suggest that FOS and its fermentation products may influence the iron absorption process, the effects of prolonged FOS supplementation on iron status remain unclear. The objective of this study was therefore to determine the enhancing effects of FOS supplementation on the iron stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, the presented results conrmed that our formula fortied by iron and supplemented with inulin could signicantly increase the blood Hb content, in particular, long-chain inulin that had a good recovery effect on the Hb content. Zhang et al 60 conrmed that anemic rats fed the lowiron diet showed a mild increase (P # 0.05) in the hemoglobin level aer 21 days of fructooligosaccharide (FOS) supplementation when compared to rats without FOS.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Therefore, the presented results conrmed that our formula fortied by iron and supplemented with inulin could signicantly increase the blood Hb content, in particular, long-chain inulin that had a good recovery effect on the Hb content. Zhang et al 60 conrmed that anemic rats fed the lowiron diet showed a mild increase (P # 0.05) in the hemoglobin level aer 21 days of fructooligosaccharide (FOS) supplementation when compared to rats without FOS.…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Some reported benefits include enhanced immune system [5] and defense against pathogens [6], modulation of short-chain fatty acid (SCFA) production [7] and tight junction integrity [8], and mild improvement in iron status [9]. Proliferation of beneficial bacteria, usually lactobacilli and bifidobacteria, in the colon of the host may also be associated with reducing lipid peroxidation in colonic mucosa of intact mammals [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, also in rats with iron deficiency anemia, it was shown that the addition of FOS in the group of rats fed an iron-deficient diet slightly improved bioavailability compared to the group without FOS. On the other hand, in the group fed a diet with proper iron content, the addition of FOS did not change the bioavailability of iron [ 40 ]. Moreover, Ohta et al, showed that FOS prevented anemia in totally gastrectomized rats [ 41 ] ( Table 2 ).…”
Section: Prebiotics In Anemiamentioning
confidence: 99%